Preferences and hiring policies for the sales personnel of drug companies - Cartagena, Salvador C.; Gumban, Glenn D.; Padios, Glory Mar B.; Panilla, Catahrine D. (2001.)
Opportunities come and go. But one must not sit down, stare up, sleep, and wait for that opportunity to knock at and wake him up. One must search for it. However, what merit does man get if he himself does not know what he is looking for? Many attempts have been made to guide individuals in their search for opportunities. This study in response, attempted to guide those who are searching for job focusing only in the field of selling. Generally, this study aimed to find what preferences and hiring policies do drug companies employ to identify the factors that influence/determine such preferences and hiring policies, how these preferences and hiring policies affect the performance of the companies, and the extent for which the drug companies hire personnel for their sales department and spend in maintaining and such sales personnel. The researchers have found the following in the course of their undertaking. The companies observe hiring policies and they prefer college graduate with good communication skills. Their preferences and hiring policies are influence by the product they sell, and some customer characteristics. such preferences and hiring policies highly affect their performance. Through, this, applicants will be guided on what to do in hunting for jobs especially those related to selling drugs.
Business Research Proposal (BA 200-Business Research). -- Iloilo City : University of the Philippines Visayas - College of Management, March 30, 2001.